Colchicine Significantly Reduces Incident Cancer in Gout Male Patients: A 12-Year Cohort Study. Issue 50 (December 2015) - Kuo, Ming-Chun; Chang, Shun-Jen; Hsieh, Ming-Chia
Abstract : Abstract: Patients with gout are more likely to develop most cancers than subjects without gout. Colchicine has been used for the treatment and prevention of gouty arthritis and has been reported to have an anticancer effect in vitro. However, to date no study has evaluated the relationship between colchicine use and incident cancers in patients with gout. This study enrolled male patients with gout identified in Taiwan's National Health Insurance Database for the years 1998 to 2011. Each gout patient was matched with 4 male controls by age and by month and year of first diagnosis, and was followed up until 2011. The study excluded those who were diagnosed with diabetes or any type of cancer within the year following enrollment. We calculated hazard ratio (HR), aged-adjusted standardized incidence ratio, and incidence of 1000 person-years analyses to evaluate cancer risk. A total of 24, 050 male patients with gout and 76, 129 male nongout controls were included. Patients with gout had a higher rate of incident all-cause cancers than controls (6.68% vs 6.43%, P = 0.006). A total of 13, 679 patients with gout were defined as having been ever-users of colchicine and 10, 371 patients with gout were defined as being never-users of colchicine. Ever-users of colchicine had a significantly lower HR of incident all-cause cancers than never-users of colchicine after adjustment for age (HR = 0.85, 95% CI = 0.77–0.94; P = 0.001). In conclusion, colchicine use was associated with a decreased risk of incident all-cause cancers in male Taiwanese patients with gout.